2007
DOI: 10.1021/jp073421c
|View full text |Cite
|
Sign up to set email alerts
|

Initial Photochemistry of Bilirubin Probed by Femtosecond Spectroscopy

Abstract: Bilirubin is a breakdown product from heme catabolism, and reduced excretion of bilirubin can lead to jaundice. Phototherapy is the most common treatment for neonatal jaundice, a condition frequently encountered in newborn infants. Knowledge of the photochemistry of bilirubin, which is dominated by (ultra)fast components, is necessary for the profound understanding of the processes in phototherapy. Here, we report results from femtosecond fluorescence upconversion measurements on bilirubin and half-bilirubin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 60 publications
0
46
1
Order By: Relevance
“…The mechanism is found to be consecutive: the shortlived Franck-Condon state forms a weakly fluorescent intermediate which decays to the ground state with a 15 ps time constant. In contrast to previous proposals, [16][17][18] the intermediate shows stronger CQC bonds than the ground electronic state, indicating that the molecular structure is not twisted.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The mechanism is found to be consecutive: the shortlived Franck-Condon state forms a weakly fluorescent intermediate which decays to the ground state with a 15 ps time constant. In contrast to previous proposals, [16][17][18] the intermediate shows stronger CQC bonds than the ground electronic state, indicating that the molecular structure is not twisted.…”
Section: Introductioncontrasting
confidence: 99%
“…Upon optical excitation, BR deactivates rapidly by internal conversion with almost negligible quantum yields for all other possible deactivation routes at room temperature. 11,12,16 fs spectroscopy [16][17][18] revealed that the deactivation process extends from the 100 fs to the 50 ps time-scales and could be facilitated by a conical intersection in Scheme 1 Three-dimensional structure of bilirubin IXa (left). Dipoledipole coupling (V ) of the localized endo and exo S 1 states explains the lowest bright states of bilirubin (right).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twisting of double bonds in the excited state is a very well-known mechanism for fast deactivation, with great relevance in biological processes, such as light detection by retinal in the visual protein rhodopsin 24 or phototherapy of neonatal jaundice. 25 Many of the observed reactions happen on a very fast time-scale, hundreds of femtoseconds to a few picoseconds. In the case of stilbene, for example, a barrierless excited state reaction is observed with time constants of ca.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been suggested that it is toxic when the amount of BR in the body exceeds the binding capacity of albumin, extra free BR binds and deposits to various tissues. Its deposition and accumulation in tissues will cause disorders in the metabolism of BR and induce various diseases . Hydroxyapatite (HAP) (Ca 10 (PO 4 ) 6 (OH) 2 ), a main constituent of bones and teeth, has been used for purification and separation of biological molecules owing to its excellent biocompatibility, slow biodegradation, good mechanical stability, great adsorption and photocatalysis property .…”
Section: Introductionmentioning
confidence: 99%